NURSING CARE WITH AROMATHERAPY IMPLEMENTATION FOR ACUTE PAIN IN PATIENTS POST SECTIO CAESAREA - Hardiyanti, Titin (Universitas Airlangga, 2022)
Introduction: Post Sectio Caesarea pain is normal for every woman because Cesar delivery is a way of giving birth to a fetus by making an incision in the uterine wall through the front wall of the abdomen or vagina. Every surgery is associated with an incision, a trauma for the patient who handles complaints such as pain. This research is a case study research with participants of post-section postpartum mothers with pain aromatherapy nursing actions. Methods: The data collection method was done by interview, observation, and medical records for four days in the Melati room of Dr Soegiri Lamongan. The data are presented in tabular form and descriptive analysis using the nursing stages. Results: The results of this case study indicate that the assessment, diagnosis, intervention, implementation, and evaluation of Post Sectio Caesarea patients are consistent with the diagnosis of primary pain. Conclusions: The reference of this study is the patient P2002 Post Sectio Caesarea can be carried out in nursing care following the theory. Suggestions for authors, nurses, hospitals, patients, and families can add relaxation techniques with lemon aromatherapy and distraction methods by watching television to deal with pain in Post section Caesarea patients.